Effect of Viewing Angle in Gamma-Ray Burst Properties - Sreelakshmi P. Chakyar; Sarath Prabhavu J; Lekshmi Resmi (The Astrophysical Journal)
The empirical classification of gamma-ray bursts (GRBs) is based on their distribution in the plane of burst duration and spectral hardness. Two distinct distributions, long-soft and short-hard bursts, are observed in this plane, forming the basis for the long and short classification scheme. Traditionally, this scheme was mapped to two different GRB progenitor classes. However, several recent bursts have challenged this mapping. This work investigates how an observer’s viewing angle relative to the jet axis influences the duration-hardness plane. We simulate single-pulse GRBs using an optically and geometrically thin homogeneous top-hat jet model. Bursts are simulated with an isotropic viewing angle distribution, and we calculate the pulse duration and spectral hardness corresponding to FERMI GBM energy bands. The viewing angle significantly impacts spectral hardness for our assumed broken power-law spectra, while its effect on duration is less pronounced. Our analysis indicates that soft and low-luminous bursts are likely off-axis events. It is possible that some of the fast X-ray transients and X-ray-rich GRBs observed by the Einstein Probe and the Space Variable Objects Monitor missions originate from off-axis jets.